Safety and tolerability of high‐intensity statin therapy in heart transplant patients receiving immunosuppression with tacrolimus. Issue 1 (18th December 2018) - Heeney, Stephanie A.; Tjugum, Shelby L.; Corkish, Morgan E.; Hollis, Ian B.
Abstract: Background: Following heart transplantation (HT), HMG CoA reductase inhibitors (statins) have been shown to reduce total and low‐density lipoprotein (LDL) cholesterol, development of cardiac allograft vasculopathy (CAV), and mortality. Studies in HT patients have demonstrated the safety of low/moderate intensity statins; however, little data exist using high‐intensity (HI) statins. The study aim was to evaluate the safety and efficacy of HI statins in HT recipients receiving tacrolimus. Methods: This single‐center, retrospective analysis included adult HT recipients from January 1, 2005, to December 31, 2015, who received HI statin therapy during posttransplant follow‐up. The primary outcome, tolerability, was defined as the absence of myalgias, hepatotoxicity, rhabdomyolysis, or HI statin dose reduction/discontinuation. The secondary end point was the mean reduction in total and LDL cholesterol. Results: Among the 24 patients included, one experienced myalgias and therapy discontinuation (4%; P  > 0.99). No other HI statin dose reduction/discontinuation occurred, and no instances of rhabdomyolysis or hepatotoxicity were observed. The average reduction in total and LDL cholesterol after conversion to HI statin was 35 mg/dL ( P  = 0.02) and 19 mg/dL ( P  = 0.10), respectively. Conclusions: High‐intensity statin therapy appears safe and efficacious in HT recipients receiving tacrolimus and is a reasonable option for the treatment of refractory hyperlipidemia.